2020
DOI: 10.1242/dmm.043364
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal microRNAs as potential biomarkers of hepatic injury and inflammation in a murine model of glycogen storage disease type 1a

Abstract: Most patients affected by glycogen storage disease type 1a (GSD1a), an inherited metabolic disorder caused by mutations in the enzyme glucose-6-phosphatase-α (G6Pase-α), develop renal and liver complications, including the development of hepatocellular adenoma/carcinoma. The purpose of this study was to identify potential biomarkers of the pathophysiology of the GSD1a-affected liver. To this end, we used the plasma exosomes of a murine model of GSD1a, the LS-G6pc−/− mouse, to uncover the modulation in microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…To identify potential biomarkers of the pathophysiology of the GSDIa-affected liver we have recently analyzed the plasma exosomes of a murine model of GSDIa in an LS- G6pc −/− mouse [ 11 ] to uncover the modulation of the microRNA expression associated with the disease [ 12 ], as well as the proteomic expression profile in the liver of the same mouse model [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify potential biomarkers of the pathophysiology of the GSDIa-affected liver we have recently analyzed the plasma exosomes of a murine model of GSDIa in an LS- G6pc −/− mouse [ 11 ] to uncover the modulation of the microRNA expression associated with the disease [ 12 ], as well as the proteomic expression profile in the liver of the same mouse model [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This animal model could provide an efficient means of discovering the diagnostic markers of hepatic tumors since the liver is the only organ affected in these mice. The results of that study revealed that the altered expression of several Exo-miRs correlated with various pathologic liver states associated with the progression of the disease, among which Exo-miRs discriminated LS- G6pc −/− mice with adenomas from LS- G6pc −/− mice without adenomas [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We chose to focus on the upregulated miRNAs. It has been reported that 6 out of the 11 upregulated miRNAs, including miR- 483-3p, miR-328-3p, let-7d-3p, miR-92b-5p, miR-381-3p, and miR-210-5p, are involved in injury and inflammation (Lin et al, 2019;Fu et al, 2020;Maemura et al, 2020;Resaz et al, 2020). Subsequently, plasma EVs from the validation cohort of 37 sepsis patients at admission and 25 healthy controls were examined for the expression of the 6 inflammation-related miRNAs via qRT-PCR.…”
Section: Evs From Sepsis Patients Have Increasedmentioning
confidence: 99%
“…Wang D et al showed that MSC-Exos targeting miR-125b could inhibit neointimal hyperplasia by activating myosin IE [10]. Moreover, the function of exosomes in cells provides multiple therapeutic applications, including cell growth and tissue injury repair following myocardial ischaemia reperfusion [11], neurological stroke [12] and inflammation [13]. In recent years, research on the mechanism of miRNA transfer, including exosomes, has attracted increasing attention [14,15].…”
mentioning
confidence: 99%